What skills are required for sustainable leadership in hospitality? - Silva, Susana (2025)
The focus of Sustainability Leadership in tourism is on fostering individual development to facilitate adaptation to emerging technologies within complex and rapidly evolving environments, ultimately aiming to enhance performance and organizational effectiveness. Sustainable leaders prioritize collaboration, consensus-building, and support for team members to collectively achieve shared objectives, particularly those set by diverse stakeholders. This qualitative study employed a semi-structured interview methodology to explore sustainability leadership within the hospitality sector. All interviews were conducted via online platforms and examined using thematic analysis. The sample included 10 hotel managers from various lodging establishments in Portugal, comprising four men (40%) and six women (60%). Participants’ ages ranged from below 30 to 50 years, with one manager under 30, five between 31 and 40, and four between 41 and 50. In the context of organizational sustainability, participants emphasized the importance of a long-term perspective, safety considerations, and corporate social responsibility. Half of the respondents indicated the presence of sustainability-specific policies, largely derived from group policies or specific sustainability-focused project requirements. Most participants reported that sustainability is integrated into their organization’s vision and mission, with several referencing the European Union Green Deal and the United Nations Sustainable Development Goals as key frameworks guiding their strategies. The majority of participants assessed their digital proficiency as advanced, even within complex operational contexts. Organizational digitalization levels were generally advanced, although some organizations were identified at an intermediate digitalization stage. Furthermore, social dimensions of sustainability and soft skills were regarded as essential for sustainable leadershipin hospitality. The most highly valued leadership soft skills included solution-oriented thinking, resilience, critical thinking, communication, and team cohesion, whereas time management was identified as a lesser priority. These findings underscore the significance of sustainability for managers in the hospitality sector, though the degree of implementation varies across lodging types and different sustainability dimensions.